Advances in respiratory physiology in mouse models of experimental asthma - Carroll, Olivia R.; Pillar, Amber L.; Brown, Alexandra C.; Feng, Min; Chen, Hui; Donovan, Chantal (Frontiers in Physiology, 2023)
Recent advances in mouse models of experimental asthma coupled with vast improvements in systems that assess respiratory physiology have considerably increased the accuracy and human relevance of the outputs from these studies. In fact, these models have become important pre-clinical testing platforms with proven value and their capacity to be rapidly adapted to interrogate emerging clinical concepts, including the recent discovery of different asthma phenotypes and endotypes, has accelerated the discovery of disease-causing mechanisms and increased our understanding of asthma pathogenesis and the associated effects on lung physiology. In this review, we discuss key distinctions in respiratory physiology between asthma and severe asthma, including the magnitude of airway hyperresponsiveness and recently discovered disease drivers that underpin this phenomenon such as structural changes, airway remodeling, airway smooth muscle hypertrophy, altered airway smooth muscle calcium signaling, and inflammation. We also explore state-of-the-art mouse lung function measurement techniques that accurately recapitulate the human scenario as well as recent advances in precision cut lung slices and cell culture systems. Furthermore, we consider how these techniques have been applied to recently developed mouse models of asthma, severe asthma, and asthma-chronic obstructive pulmonary disease overlap, to examine the effects of clinically relevant exposures (including ovalbumin, house dust mite antigen in the absence or presence of cigarette smoke, cockroach allergen, pollen, and respiratory microbes) and to increase our understanding of lung physiology in these diseases and identify new therapeutic targets. Lastly, we focus on recent studies that examine the effects of diet on asthma outcomes, including high fat diet and asthma, low iron diet during pregnancy and predisposition to asthma development in offspring, and environmental exposures on asthma outcomes. We conclude our review with a discussion of new clinical concepts in asthma and severe asthma that warrant investigation and how we could utilize mouse models and advanced lung physiology measurement systems to identify factors and mechanisms with potential for therapeutic targeting.